2007
DOI: 10.1103/physreve.75.036216
|View full text |Cite
|
Sign up to set email alerts
|

Signature of ray chaos in quasibound wave functions for a stadium-shaped dielectric cavity

Abstract: Light emission from a dielectric cavity with a stadium shape is studied in both ray and wave models. For a passive cavity mode with low loss, a remarkable correspondence is found between the phase space representation of a quasibound wave function and its counterpart distribution in the ray model. This result provides additional and more direct evidence for good ray-wave correspondence in low-loss modes previously observed at the level of far-field emission pattern comparisons.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 22 publications
5
48
0
Order By: Relevance
“…We choose the case L = R which is the most chaotic one [44]. The spatial structure of optical modes in microstadiums has been extensively studied in the context of ray-wave correspondence in open systems [45,46,47,48,49]. Our aim is to study the spectral properties of modes in such a kind of cavity.…”
Section: The Microstadiummentioning
confidence: 99%
See 2 more Smart Citations
“…We choose the case L = R which is the most chaotic one [44]. The spatial structure of optical modes in microstadiums has been extensively studied in the context of ray-wave correspondence in open systems [45,46,47,48,49]. Our aim is to study the spectral properties of modes in such a kind of cavity.…”
Section: The Microstadiummentioning
confidence: 99%
“…The unstable manifold therefore describes the route of escape from the chaotic system. For the case of chaotic microcavities it has been demonstrated that the unstable manifold can play an important role for the far-field emission pattern [48,52,53,54,55].…”
Section: B the Chaotic Repellermentioning
confidence: 99%
See 1 more Smart Citation
“…Partial barrier localization [2][3][4][5] and the suppression of multiphoton ionization [6] are well-known examples. This suppression phenomenon would become more conspicuous when a Hamiltonian system takes a gradual transition to chaos so that the action transport by chaotic dynamics also increases along the chaotic transition [7,8].Recently, many works have converged to a consensus that the emission directionality in chaotic deformed microcavities is well explained by classical ray dynamics in phase space [9][10][11][12][13][14][15][16]. However, the evanescent leakage from a symmetric or slightly deformed microcavity is inexplicable by the classical dynamics [17], and thus it is of considerable interest to understand how emission mechanism changes along the chaotic transition.…”
mentioning
confidence: 99%
“…Recently, many works have converged to a consensus that the emission directionality in chaotic deformed microcavities is well explained by classical ray dynamics in phase space [9][10][11][12][13][14][15][16]. However, the evanescent leakage from a symmetric or slightly deformed microcavity is inexplicable by the classical dynamics [17], and thus it is of considerable interest to understand how emission mechanism changes along the chaotic transition.…”
mentioning
confidence: 99%